Effect on Dimensions of Health Services to Inpatient Satisfaction at Primary Health Care - Dianing Negari, Ayu Rahajeng; Nurida, Annisa; Ghufron, Musa; Anas, Muhammad (Universitas Muhammadiyah Semarang, 2021)
Background: Satisfaction is a feeling that the consumers feel when the service they receive meets or surpass their expectations. Public satisfaction with health care services is still a significant issue for health institutions in improving the service quality. Despite various efforts that health care providers have made, some residents in an area were unsatisfied with the health services in their environment.Objective: To determine the effect of the dimensions of health service quality on patient satisfaction at the Primary Health Care 1 Melaya, Jembrana, BaliMethod: Analytical observational study, a cross-sectional design. The total sample was 70 respondents. Data collection was performed using questionnaires. Multiple linear regression was used to analyze the average value of patient satisfaction based on the five dimensions of quality of health care.Result: The dimensions of tangibility, responsiveness, assurance, and empathy have a significance value (p<0.05), while the reliability dimension has no significance value (p>0.05). So the formula used to predict patient satisfaction with health services received is as follows:y = 0,352+0,295*X1–0,104*X2–0,201*X3+0,334*X4+0,180*X5The dimension of health services that has the largest influence on the satisfaction of inpatients is assurance. Patients feel assured and satisfied when the health workers communicate their expertise and competencies before doing their work.Conclusion: Tangibility, reliability, responsiveness, and assurance were four of five dimensions of health services that have significantly influenced the satisfaction of inpatients.